Does primary resource-based industrialisation offer an escape from underdevelopment? - Ali, Fatimah (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2006)
It is commonly believed about sub-Saharan Africa (SSA) that the region has a comparative advantage in primary resources as reflected by its high share of primary exports to total exports. In acknowledging the region's comparative advantage, the study tries to put the determinants from the Wood and Mayer (1998, (999) (W-M) Heckscher-Ohlin based model in the context of two relatively diversified countries (South Africa and Mauritius) and two commodity-export-dependent countries of sub-Saharan Africa (Nigeria and CÃ´ÌŒÌŒte d'Ivoire). The study finds that the skill and land resource measures used in the W -M (1998, 1999) thesis do not explain why Nigeria, having a similar level of skill per worker ratio to South Africa, has not diversified. Further, Mauritius having relatively the highest skill per land ratio specialises in low-skill textiles and clothing, while South Africa specialises in the more human capital-intensive "other manufactures" group. The other measure, a low land per worker ratio that explains Mauritius' relatively higher share of manufacturing exports, also fails to apply to Nigeria. The thesis thus concludes that the W-M land and skill measures could only be rough proxies in determining comparative advantage in manufacturing exports. However, employing the Dutch disease hypothesis recognises the potential of land abundance as a natural resource, namely minerals in South Africa, oil in Nigeria, and cocoa in CoÌŒÌŒte d'Ivoire. The Dutch disease is a dynamic process of structural economic and political development that will permit an understanding of why natural resource abundant countries do not have a comparative advantage in manufacturing, at least in the short to medium term. The study therefore investigates commodity dependence and the Dutch disease effects to examine whether primary resource- based industrialisation offers an escape from underdevelopment. It establishes that South Africa, a mineral resource rich country, diversified based on a broad mineral-energy-complex (MEC) reinforcing the notion that land abundant countries will first invest in capital- intensive primary resource processing. However, the thesis concludes that in Nigeria and CoÌŒÌŒte d'Ivoire where external shocks are more predominant probably because of single commodity export reliance, the manufacturing sector lags behind more due to resource and spending effects that a natural resource boom generates in these economies.
Keywords: Comparative advantage (International trade); Exports -- Africa, West; Exports -- Mauritius; Exports -- South Africa; Foreign trade promotion -- Mauritius; International trade; Primary commodities -- Africa; Human capital -- Economic aspects -- Africa; Natural resources -- Africa; Africa -- Commerce